First Report of TTSuV1 in Domestic Swiss Pigs - Sabrina Polster; Julia Lechmann; Julia Lienhard; Deborah Peltzer; Barbara Prähauser; Claudia Bachofen; Frauke Seehusen (Viruses, 2022)
Serum prevalence of Torque teno sus viruses (TTSuV1 and k2; family Anelloviridae) is known to be high in the porcine population worldwide but pathogenesis and associated pathomorphological lesions remain to be elucidated. In this study, quantitative real-time PCR for detection of TTSuV1 was performed in 101 porcine samples of brain tissue, with animals showing inflammatory lesions or no histological changes. Additionally, a pathomorphological and immunohistochemical characterization of possible lesions was carried out. Selected cases were screened by TTSuV1 in situ hybridization. Furthermore, TTSuV1 quantitative real-time PCR in splenic and pulmonary tissue and in situ hybridization (ISH) in spleen, lungs, mesenteric lymph node, heart, kidney, and liver were performed in 22 animals. TTSuV1 was detected by PCR not only in spleen and lung but also in brain tissue (71.3%); however, in general, spleen and lung tissue displayed lower Ct values than the brain. Positive TTSuV1 results were frequently associated with the morphological diagnosis of non-suppurative encephalitis. Single TTSuV1-positive lymphocytes were detected by ISH in the brain but also in lungs, spleen, mesenteric lymph node and in two cases of non-suppurative myocarditis. A pathogenetic role of a TTSuV1 infection as a co-factor for non-suppurative encephalitides cannot be ruled out.